CARBON ISOTOPE EFFECTS IN THE OPEN-SYSTEM FISCHER-TROPSCH SYNTHESIS - Taran Y.A.; Kliger G.A.; Sevastianov V.S. (My University, 2007)
Carbon isotopic composition was measured for products of the Fischer-Tropsch synthesis: catalytic reaction between CO and H2 to produce CO, CO2, light hydrocarbons C1-C4 and "oil" fraction. Hydrogen isotopes were also measured in the oil fraction and the produced water. Experimental runs were conducted in the flow-through reactor at 260-310 °C and 30 bar using the synthesis gas composed of 5N2 + 3H2 + 2CO, on Fe-catalyst mixed with ZSM-5 synthetic zeolite. In the two of seven runs a Fe + Co-catalyst was used that gives a lower yield of unsaturated hydrocarbons in reaction products. The isotopic effects depended on the conversion of the carbon monoxide. Under steady-state conditions (CO conversion more than 90%) a strong kinetic fractionation was observed between CO and CO2 (~-10‰) and CO and hydrocarbons (~+38‰). At low conversion a clear "inverse" isotopic trend of the depletion in 13C of longer hydrocarbon chains was observed. On average, Δ12 = δ13C(CH4) - δ13C(C2H6) correlates well with the CO conversion: the C2H6 is ~6‰ isotopically lighter than CH4 at low conversion and ~2‰ heavier at steady-state regime. Under steady-state conditions there almost no difference was observed in the isotopic composition of methane and ethane and higher hydrocarbons. The chemical composition of light hydrocarbons in the products of flow-through, dynamic FTS is different from that found in the static FTS-type experiments with Fe-catalyst, but isotopic effects are similar. Our results suggest that the isotopic distribution of carbon found in so-called "abiogenic" hydrocarbons from some natural gases (δ13C1 > δ13C2 > δ13C3 >⋯) is somewhat similar to that at low conversion of CO, but do not resemble the distribution characteristic for the high conversion products, at least, on Fe-catalyst. Other processes (a simple mixing of two or more endmembers) or other P-T conditions of the carbon reduction could be responsible for the "inverse" isotopic trend found in meteorites and some natural gases. © 2007 Elsevier Ltd. All rights reserved.